What town planners do : exploring planning practices and the public interest through workplace ethnographies - Schoneboom, Abigail; Slade, Jason; Tait, Malcolm; Vigar, Geoff (Policy Press, 2023)
Presenting the complexities of doing planning work, with all its attendant moral and practical dilemmas, this rich ethnographic study analyses how places are made through stories of four diverse public and private sector working environments. The book provides a unique insight for educators, students and researchers into the everyday lives of planners and those in associated built environment occupations. This exceptional account of the micro-politics of a knowledge-intensive profession also provides an excellent resource for sociologists of contemporary work. The authors use team ethnography to push the methodological frontiers of planning research and to advance organisational ethnography into new areas.